Commonly dispensed herbal medicinal products and their source of information for practice in community pharmacies in Ethiopia: Promoting evidence‐based practice in health‐care settings. Issue 1 (6th January 2021) - Emiru, Yohannes Kelifa; Ayele, Asnakew Achaw; Tefera, Yonas Getaye; Siraj, Ebrahim Abdela; Girma, Habtamu; Lilay, Melaku; Girma, Tinsae; Belachew, Sewunet Admasu; Gebresillassie, Begashaw Melaku
ABSTRACT: Aim: The objective of this study was to assess commonly dispensed herbal medicinal products (HMPs) and their sources of information for practice at Ethiopian community pharmacies in the light of promoting evidence‐based practice in health‐care settings of the nation. Methods: A cross‐sectional survey was conducted at community pharmacies in Northwest Ethiopia from February to April 2019. Data collection was carried out using a structured self‐administered Yesquestionnaire. Demographic data and pharmacists' range of HMPs and information sources were evaluated using descriptive analysis. The chi‐squared test was used to find correlations of demographic variables with sells and accessibility of information regarding HMPs. A P ‐value of less than 0.05 represents a significant difference. Results: The study results show that 100 (86.2%) of the community pharmacists had dispensed various class of HMPs at their practice site and 71 (61.2%) pharmacists accessed HMP information. The majority of accessible HMP information sources at community pharmacies were package inserts/brochures and internet websites. Regarding the categorical class of regularly dispensed products, more than 50% were dermatological products. Regarding their customers' inquiries regarding HMPs, 76.7% of respondents get queries related to HMPs during the dispensing period. Dispensing practice was significantly correlated with employment status ( P = 0.021) and any previous continuing education on HMPs ( P < 0.01) but accessibility of HMP information was only correlated with employment status ( P = 0.044). Conclusions: The evidence of these findings suggests that HMPs are increasingly dispensed as therapeutic agents with inadequate delivery of evidence‐based information in community pharmacies of Ethiopia.